Kolaborasi Guru PAI dan Guru BK dalam Menanamkan Nilai Akhlakul Karimah pada Forum Annisa di SMK Negeri 2 Padang Panjang - Rida Dwi Cahyani; Januar (Lembaga Yasin AlSys, 2026)
Although collaboration between Islamic Religious Education (PAI) teachers and Guidance and Counseling (BK) teachers plays an important role in students’ character development, studies examining their collaboration through Forum Annisa activities in vocational high schools (SMKs) remain limited. This study aimed to analyze the forms of collaboration between PAI and BK teachers in instilling akhlakul karimah values through Forum Annisa and to identify the factors supporting and hindering its implementation at SMK Negeri 2 Padang Panjang. This study employed a qualitative approach using a descriptive method and a field research design. The key informants comprised PAI and BK teachers, whereas the supporting informants included students participating in Forum Annisa, the Vice Principal for Student Affairs, and the principal. Data were collected through observation, interviews, and documentation and were subsequently analyzed through data reduction, data display, conclusion drawing, and verification. Data credibility was established through methodological and source triangulation. The findings showed that collaboration was implemented through joint program planning, the division of tasks and roles, communication and coordination, the implementation of character-building activities, the provision of guidance and motivation, mentoring, role modeling, and evaluation. The implementation of this collaboration was supported by effective communication, shared goals, school support, task allocation, the availability of facilities, and teacher role modeling. The inhibiting factors included time constraints, limited interest among some students, differences in students’ characteristics and backgrounds, environmental and social media influences, and the lack of a structured evaluation process. This study confirms that planned collaboration between PAI and BK teachers is an essential component of instilling akhlakul karimah values through Forum Annisa. These findings contribute to the development of research on interteacher collaboration in character development and provide practical implications for schools to strengthen coordination and establish a more structured program evaluation system.